The Strategies of the Movement for the Liberation of Lithuania - Gaškaitė-Žemaitienė, Nijolė (Genocidas ir rezistencija, 1999)
What were the strategic objectives of the leadership of the total resistance to occupation in Lithuania in 1944–1953? The main objective must have been very clear: to restore an independent state. However, this aspiration of the Lithuanian nation clashed with the interests of other geopolitical factors, namely the Soviet Union and the Western powers, which were trying to maintain peace and a balance of power on the European continent in the aftermath of the Second World War. The international situation and the behaviour of the occupier forced the partisans to reconsider their strategy. Time dictated three directions of resistance strategy: 1) to formulate the tasks of the nation and the resistance in the event of a prolonged occupation; 2) to predict the tactics to be used during liberation; and 3) to model the future political landscape of a restored independent state. The leadership of the partisan resistance had to address all three strategic tasks. Initially, the second and the third were more relevant, but after two or three years of occupation, the first became a priority, and from 1949, with the formation of the Movement for the Struggle for Lithuanian Freedom (LLKS), the third was almost completely abandoned.
Keywords: Soviet occupation; armer resistance; partisans; Movement of Liberation of Lithuania